PENGARUH KOMPETENSI, INDEPENDENSI, DAN PROFESIONALISME AUDITOR TERHADAP KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERASI - Sri Rahayu Indah Azhari; Asriani Junaid; Julianty Sidik Tjan (INVOICE : JURNAL ILMU AKUNTANSI, 2020)
The aim of this research is to analyse the influence of competence, independence, and professionalism on audit quality. It also analyses how the auditor ethics can moderate those independent variables to dependent variable. This research carried out on the representative of Badan Pengawasan Keuangan dan Pembangunan (BPKP) of West Sulawesi Province with 75 auditors as the respondent. The study used questionnaire as the data collecting method. Then it analysed by using multiple regression analyses dan moderated regression analysis (MRA). The results of the reseach showed that competence, independence, and professionalism effect significantly the audit quality. Auditor ethics is able to moderate the influence of competence and independence to audit quality. Auditor ethics is unable to moderate the influence of professionalism to audit quality.